A simple model to engineer single-molecule conductance of acenes by chemical disubstitution. Issue 2 (15th December 2021) - Fallaque, Joel G.; Rodríguez-González, Sandra; Díaz, Cristina; Martín, Fernando
Abstract : Single-molecule conductance of π-conjugated acenes can be engineered by changing their length, the nature of the linkers and their relative positions following the variations in the HOMO energies, as dictated by a simple extended-Hückel method. Abstract : Understanding and controlling electrical conductivity at the single-molecule level is of fundamental importance for the development of new molecular electronic devices. This ideally requires considering the many different options offered by the molecular structure, the nature of the electrodes, and all possible molecule-electrode anchoring configurations, which is experimentally tedious and theoretically very expensive. Here we present a systematic theoretical study of the conductance of di-amino, di-methylthio and di-(4-methylthio)phenyl acenes, from benzene to pentacene, and for all possible distributions of two identical linkers symmetrically placed on opposite sides of the same ring. We show that, for all investigated compounds, the relative variation of the conductance is well explained by the variations of the HOMO energies as predicted by a simple extended-Hückel approach, i.e., without the need for further input from more elaborate calculations. The model predicts quite nicely that diamino acenes are better conductors than their corresponding dimethylthio analogues, and both much better than the di-(4-methylthio)phenyl counterparts, irrespective of the linkers' relative positions. It also predicts, for a given pair of linkers, the variations in the conductance resulting from changing the acene size and/or the relative position of the linkers. These variations can be as large as an order of magnitude, and therefore can be used to engineer molecular conductance. Finally, we show that a similar approach should be useful to predict trends in the relative conductance of a large variety of disubstituted acene isomers, including various linkers.